2015
DOI: 10.3390/ijerph121215018
|View full text |Cite
|
Sign up to set email alerts
|

A Scoping Review of Maternal and Child Health Clinicians Attitudes, Beliefs, Practice, Training and Perceived Self-Competence in Environmental Health

Abstract: Clinicians regularly assess, diagnose and manage illnesses which are directly or indirectly linked to environmental exposures. Yet, various studies have identified gaps in environmental assessment in routine clinical practice. This review assessed clinicians’ environmental health practices, attitudes and beliefs, and competencies and training. Relevant articles were sought using a systematic search strategy using five databases, grey literature and a hand search. Search strategies and protocols were developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…Few pregnant women were counselled about the environment by health providers. Several studies have shown that perinatal health providers do not generally ask patients about their environmental exposure, except for the consumption of toxic substances [30,31]. An American survey found that less than 20% of obstetricians routinely interview their patients about their environment [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few pregnant women were counselled about the environment by health providers. Several studies have shown that perinatal health providers do not generally ask patients about their environmental exposure, except for the consumption of toxic substances [30,31]. An American survey found that less than 20% of obstetricians routinely interview their patients about their environment [32].…”
Section: Discussionmentioning
confidence: 99%
“…An American survey found that less than 20% of obstetricians routinely interview their patients about their environment [32]. The difficulties most frequently cited were the lack of training and knowledge in environmental health, the lack of evidence-based information, the short duration of consultations [30,31,32,33], the fear of patient reactions, and the lack of solutions [33].…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to tobacco exposure during pregnancy, which remains the principal risk referred to by perinatal health professionals [6], exposure to emergent risks is not mentioned in the existing French existing guidelines [1] but in American’s [7].…”
Section: Introductionmentioning
confidence: 99%
“…The adaption of education to these determinants is a necessity [19]. Health professionals ought to perform educational tasks, but consultation time, educational tools, and psychosocial training are insufficient [23].…”
Section: Introductionmentioning
confidence: 99%